Triglyceride/High-Density Lipoprotein Ratio as a Predictor of Major Cardiovascular Events Within 6 Months Post-Treatment in Patients with Acute Myocardial Infarction and Type 2 Diabetes Mellitus at Haji Adam Malik General Hospital, Medan - Taufik, Yasdika Imam; Hasan, Refli; Akbar, Nizam Zikri (Journal of Society Medicine, 2025)
Introduction: Cardiovascular disease (CVD) remains the leading global cause of death, with coronary artery disease (CAD) and stroke contributing to 15 million deaths in 2016. Type 2 diabetes mellitus (DM) increases the risk of complex CAD, characterized by diffuse, calcified, and multivessel lesions. While the triglyceride (TG)/high-density lipoprotein cholesterol (HDL-C) ratio is a potential independent predictor of CVD, its prognostic value for mortality in diabetic CAD patients undergoing statin therapy remains unclear. This study aimed to analyze the association between the TG/HDL-C ratio and cardiovascular and all-cause mortality in this population. Methods: This cross-sectional analytical study examined the relationship between the TG/HDL-C ratio and major cardiovascular events in non-ST-elevation acute coronary syndrome (NSTE-ACS) patients with type 2 DM receiving statin therapy. Data were collected through clinical observation and medical records. Statistical analysis utilized the Chi-square or Fisher’s Exact test to assess associations, with statistical significance defined as p <0.05. Results: The study included 72 patients (72.2% male; mean age 58.6±8.5 years) with type 2 DM (mean duration 10.5±3.9 years) and acute coronary syndrome (61.1% NSTEMI). Among participants, 61.1% were smokers, 48.6% had hypertension, and lipid profiles revealed 100% hypertriglyceridemia, 87.5% elevated LDL, and 33.3% low HDL. A high TG/HDL ratio was observed in 72.2% of subjects and was significantly associated with major adverse cardiovascular events (OR=3.32; p=0.025), indicating a 3.32-fold higher risk in the high TG/HDL ratio group. Conclusion: The TG/HDL-C ratio can serve as an effective parameter for estimating the risk of MACE in ACS patients with T2DM.